Braf mutation induces rapid neoplastic transformation in the aged and aberrantly methylated intestinal epithelium. Issue 6 (6th July 2021) - Fennell, Lochlan; Kane, Alexandra; Liu, Cheng; McKeone, Diane; Hartel, Gunter; Su, Chang; Bond, Catherine; Bettington, Mark; Leggett, Barbara; Whitehall, Vicki
Abstract : Objective: Sessile serrated lesions (SSLs) are common across the age spectrum, but the BRAF mutant cancers arising occur predominantly in the elderly. Aberrant DNA methylation is uncommon in SSL from young patients. Here, we interrogate the role of ageing and DNA methylation in SSL initiation and progression. Design: We used an inducible model of Braf mutation to direct recombination of the oncogenic Braf V637E allele to the murine intestine. BRAF mutation was activated after periods of ageing, and tissue was assessed for histological, DNA methylation and gene expression changes thereafter. We also investigated DNA methylation alterations in human SSLs. Results: Inducing Braf mutation in aged mice was associated with a 10-fold relative risk of serrated lesions compared with young mice. There were extensive differences in age-associated DNA methylation between animals induced at 9 months versus wean, with relatively little differential Braf- specific methylation. DNA methylation at WNT pathway genes scales with age and Braf mutation accelerated age-associated DNA methylation. In human SSLs, increased epigenetic age was associated with high-risk serrated colorectal neoplasia. Conclusions: SSLs arising in the aged intestine are at a significantly higher risk of spontaneous neoplastic progression. These findings provide support for a new conceptual model for serrated colorectal carcinogenesis, whereby risk of Braf- induced neoplastic transformation is dependent on age and may be related to age-associated molecular alterations that accumulate in the ageing intestine, including DNA methylation. This may have implications for surveillance and chemopreventive strategies targeting the epigenome.